Investigation of RF Signal Energy Harvesting - Soudeh Heydari Nasab; Mohammad Asefi; Lutfi Albasha; Naser Qaddoumi (Active and Passive Electronic Components)
The potential utilization of RF signals for DC power is experimentally investigated. The aim of the work is to investigate the levels of power that can be harvested from the air and processed to achieve levels of energy that are sufficient to charge up low-power electronic circuits. The work presented shows field measurements from two selected regions: an urbanized hence signal congested area and a less populated one. An RF harvesting system has been specifically designed, built, and shown to successfully pick up enough energy to power up circuits. The work concludes that while RF harvesting was successful under certain conditions, however, it required the support of other energy harvesting techniques to replace a battery. Efficiency considerations have, hence, placed emphasis on comparing the developed harvester to other systems.